Systemic therapies in metastatic pancreatic neuroendocrine neoplasms (PNENs): is there a right sequence? A case report and review of the literature. - Spada, Francesca; Gelsomino, Fabio; Fontana, Annalisa; Luppi, Gabriele; Frezza, Anna Maria; Ungaro, Antonio; Fazio, Nicola (European Journal of Oncology and Environmental Health, 2016)
Management of pancreatic neuroendocrine neoplasms (PNENs) is very complex and heterogenous; therefore the right therapeutic strategy closely depends on a multidisciplinary approach. We report a case of 35-years-old man with advanced pancreatic neuroendocrine tumours (PNET). At beginning individual specialists planned earliest treatments. After disease progression the clinical strategy was handled within a multidisciplinary team and the patient received several therapies thanks to integration of team expertise. The patient died after 7 year from the diagnosis.